Indicadores de evolução do desenvolvimento de crianças com transtorno do espectro do autismo em um serviço especializado em reabilitação intelectual - Magalhães, Luciana de Souza Rodrigues (2019)
Introduction: Autism Spectrum Disorder is a neurodevelopmental disorder that has as its essential features: persistent impairments in social communication and social interaction, restricted and repetitive patterns of behavior, interests or activities. Objective: To analyze the developmental indicators of the development of children with autistic spectrum disorder in a service specialized in intellectual rehabilitation. Methodology: This is a cross-sectional study with analytical approach of secondary data from medical records of children with autism. The study included medical records of children aged 1 to 7 years diagnosed with ASD attended twice a week by the unit's multidisciplinary team during the years 2015 to 2017. A collection instrument based on medical record information was used to monitor the indicators. of children and therapeutic evolution Autism Treatment Evaluation Checklist. Data were analyzed using Jamovi version 2018 and the results were presented as graphs and tables. A mean score of 64.7 was observed in the initial ATEC and after 12 months of intervention there was a decrease in the average total score of 121 children to 56. Results: The study included 121 children with a defined clinical diagnosis for Autism Spectrum Disorder according to the classification. ICD-10 and DSM - V. Among the 121 participants, 81% were boys (n = 98) and 19% were girls (n = 23). The initial ATEC score was 64.7 and after 12 months of intervention there was a decrease in the average total score of 121 children to 56. Conclusion: The results of the study concluded that both groups of children (male and female) decreased ATEC score over time, mainly in the Speech / Language / Communication, Social and Cognitive / Sensory Awareness aspects.